Re-investigation of the sector collapse timing of Usu volcano, Japan, inferred from reworked ash deposits caused by debris avalanche - Nakagawa, Mitsuhiro; Matsumoto, Akiko; Yoshizawa, Mitsuki (Frontiers in Earth Science, 2022)
It is essential to reveal the timing of the sector collapse of a volcanic edifice to evaluate not only the evolution of a volcanic system but also volcanic hazards. Thus, it is necessary to determine the age of debris avalanche deposits caused by sector collapse. However, it is common for juvenile material to be included in these deposits. Thus, it is difficult to determine the precise and reliable age of sector collapse. The Usu volcano is a post-caldera volcano of the Toya caldera and has been constructed since 19-18 ka on the basement of the caldera-forming Toya pyroclastic flow deposits (Tpfl deposit:106 ka). A sector collapse occurred after the formation of a stratovolcano and produced the Zenkoji debris avalanche (ZDA) deposit. The reported ages for the ZDA deposits in previous studies ranged from >20 to 6 ka. We investigated the tephrostratigraphy of the soil above the ZDA deposit and surrounding area. We then recognized fine ash fall deposits at two locations, on and east of the ZDA deposit. The glass shards in these deposits were mainly derived from Tpfl, accompanied by several other tephra layers. Thus, these ash deposits should be considered reworked tephra. A considerable number of hummocks in the ZDA deposit were composed of deformed and fragmented Tpfl deposits. This suggests that the ZDA bulldozed the Tpfl deposit on the flank of the volcano. Deformation and fragmentation of the deposit would produce an ash cloud during the flow of the ZDA because Tpfl is a non-welded soft silicic deposit. The ash cloud formed a glassy, fine, ash fall deposit. Radiocarbon dating of soil samples just below and above the reworked ash deposits clarified that sector collapse occurred at 8 ka. This age is much younger than the recently proposed results. Thus, the proposed model for the mechanism of the sector collapse will be revised. It should be emphasized that reworked ash layers caused by the flow of a debris avalanche could be an indicator of the timing of a sector collapse of a volcano.